Does competition management improve the ecophysiological response to water shortage of mixed woodland species of North Patagonia? - Varela, Santiago Agustin; Diez, Juan Pablo; Letourneau, Federico Jorge; Bianchi, Emilio; Weigandt, Mariana Noemi; Porté, A.J.; Sergent, Anne Sophie; Nacif, Marcos E.; Garibaldi, Lucas Alejandro; Fernandez, María Elena (Elsevier, 2023)
Globally, the increasing forests vulnerability and drought-induced forest mortality events, extended to a larger scale, may have the potential to rapidly alter forest functioning and the provision of ecosystem services. Patagonian forests in Southern South America constitute an extensive reservoir of wildlife, but at the same time they have high productive potential. These low-mixed forests are composed of co-dominant species that are highly disturbed by local population, both for cattle raising and wood extraction; and different efforts are being dedicated to improve their management. Very little is known about the response of their different woody species to climatic variation, particularly to severe drought in particular, that may guide management strategies to improve productivity and resilience in context of drought stress and climate change. The present study aimed at characterizing the physiological strategies of response to drought to identify the most vulnerable and most resilient species to drought and how they respond under different competition levels. The response of four species of the Andean Patagonian low mixed forest was quantified at three moments of the 2018–2019 growing season in three sites through measurements of the net carbon exchange, vulnerability to xylem cavitation, tissue water relations, and damage of the photosynthetic apparatus. Additionally, records of average monthly values of precipitation and air temperature were used to calculate a standardized precipitation-evapotranspiration index. The normal climatic conditions of NW Patagonia region are characterized by water deficits during the spring-summer growing season, but the studied season presented lower values of standardized precipitation-evapotranspiration index respect to the historical mean values, indicating drier than normal conditions. Analysis of the tissue water relations showed that, in all cases, competition had no effect over the different studied parameters. There were species-specific differences in the models fitted to the vulnerability to cavitation curves; as a whole, all the species differed from each other. Overall, for all the physiological response traits studied, the Site, Species, and Season factors were important predictors in the minimum adequate model. Although there is an effect of competition on the individual annual growth, that effect is not evidenced in physiological variables of punctual measurement. Our results suggest that the effect of summer drought cannot be modulated by density management. The productivity of the species of interest can be improved, but not their adaptability, at least to severe events such as the one of the year of study.